ISPC Comments on the CGIAR Open Access Policy (June 2013 Draft) - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2013)
The document provides the ISPC's comments and feedback on the June 2013 draft CGIAR Open Access and Data Management Policy.